Effects of the peeled cassava (Manihot esculenta) form and soaking treament on removal of hydrogen cyanide from cassva flour - Palla, Charles Feb Quilantang
The study investigated the effects of (1) peeled cassava form (chips, grated and strips), and soaking treatment (unsoaked and soaked) on the removal of hydrogen cyanide (HCN) from freshly prepared cassava flour.